Rekonstruksi Metafisika Seyyed Hossein Nasr dan Pendidikan Spiritual - Azaki Khoirudin (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
This article examines Seyyed Hossein Nasr’s thought on metaphysics and its relation to spiritual education. Nasr’s paradigm is based on the universality and absolute dimension of Islam. Nasr utilizes Islamic intellectual tradition such as kalam, philosophy and mysticism as a tool to explain Islamic teachings. As a disciple of Shuhrawardi’s philosophy of illumination, Nasr proposes a concept called scientia sacra as an authentic knowledge because it is derived from the Quran and human intellect. Scientia sacra appears in the form of “al-‘ilm al-hudluri”. As regard crises faced by modern human beings, the forgotten tradition derived from Islamic sufism should be included in the current Islamic education model as an answer to the thirst for spirituality among modern humankinds. Keywords: metaphysics, scientia sacra, spiritual education, Seyyed Hossein Nasr